Flow rate and stroke volume index as predictors of mortality in patients undergoing transcatheter aortic valve implantation. (25th November 2020) - Abdelrazek, S; Hein, M; Sopira, M; Neumann, F.-J; Jander, N; Minners, J
Abstract: Background: Reduced flow rate and stroke volume are a common finding in patients with severe aortic stenosis. The aim of this study was to assess their impact on mortality in patients undergoing transcatheter aortic valve implantation (TAVI). Methods: A total of 1080 patients with severe aortic stenosis who underwent TAVI between 2007 and 2017 were followed for a mean of 2.4±1.6 years. Patients were allocated into two groups according to flow rate (cut-off 200mL/s), 805 patients had a normal flow rate and 275 patients had reduced flow rate. Long-term survival was summarized using Kaplan-Meier curves and Cox-regression models. Results: Patients with reduced flow rate were older (83.8±5.5 years; P<0.01) with more diabetics (36.7% P=0.02). Kaplan-Meier survival curves demonstrated inferior survival for patients with reduced flow rate (global log rank, P<0.01), Multivariable Cox-regression analysis (adjusted for age, creatinine, diabetes, hemoglobin and presence of atrial fibrillation) confirmed flow rate as an independent risk factor of all-cause mortality (HR: 0.998; 95%-CI: 0.997–0.999; P<0.01). Similar results were obtained for stroke volume index (SVI). Conclusion: Patients with a reduced flow rate exhibit an increased mortality even after TAVI (similar to patients with reduced SVI) and should therefore be carefully evaluated in the heart-team. Funding Acknowledgement: Type of funding source: None